Neurotoxic syndrome induced by clomipramine plus risperidone in a patient with autistic spectrum disorder: serotonin or neuroleptic malignant syndrome?. Issue 1 (December 2015) - Nikolaou, Kalliopi; Gournellis, Rossetos; Michopoulos, Ioannis; Dervenoulas, Georgios; Christodoulou, Christos; Douzenis, Athanasios
Abstract To the best of our knowledge, there are no case studies of serotonin syndrome (SS) in patients with autism spectrum disorder. We report the case of a 33-year-old male who presented SS under the combined use of clomipramine and risperidone. More specifically, within 2 days after clomipramine (10 mg/BID-two times a day) was added to risperidone (4 mg/OD-once a day), mirtazapine 45 mg/OD and alprazolam (0, 5 mg/TID-three times a day) he began to present mental, neurological and autonomic symptoms. All his psychopathological manifestations and laboratory findings normalized after the above-mentioned drugs' discontinuation, and the administration of supportive medical care and lorazepam 2, 5 mg/TID. The diagnosis of serotonin syndrome was challenging due to the relatively low dose of clomipramine, an increase of risperidone which had taken place before clomipramine administration and clinical symptoms which could be attributed to both serotonin and neuroleptic malignant syndrome.